Orbital inflammatory pseudotumor: new advances in diagnosis, pathogenesis, and treatment - Yenan Fang; Bingyan Shen; Qin Dai; Qiqi Xie; Wencan Wu; Min Wang (European Journal of Medical Research, 2023)
Abstract Orbital inflammatory pseudotumor (OIP) is a benign, non-specific inflammatory disorder that commonly occurs in middle-aged adults and is usually unilateral but can occur bilaterally. Its clinical manifestations have tremendous clinical heterogeneity and vary according to the site of infiltration and the degree of lesions, including orbital pain, swelling, diplopia, proptosis, restricted eye movement, and decreased visual acuity. Clinical features, Image characteristics and pathological examinations often need to be evaluated to confirm the diagnosis. Currently, there is no systematic research on the pathogenesis of OIP, which may be related to immunity or infection. The first-line treatment is glucocorticoids. Radiotherapy, immunosuppressants, and biologics can be considered for treatment-resistant, hormone-dependent, or intolerant patients. In this review, we aim to summarize and focus on new insights into OIP, including new diagnostic criteria, pathogenesis, and discoveries in new drugs and treatment strategies. In particular, we highlight the literature and find that T cell-mediated immune responses are closely related to the pathogenesis of OIP. Further exploration of the mechanism and signaling pathway of T cells in the immune process will help to identify their therapeutic targets and carry out targeted therapy to treat refractory OIP and reduce the side effects of traditional treatments.